Studying the effects of asymmetry on freestyle swimming using smoothed particle hydrodynamics. Issue 7 (18th May 2020) - Cohen, Raymond C. Z.; Cleary, Paul W.; Mason, Bruce R.; Pease, David L.
Abstract: The use of asymmetrical strokes is common in freestyle swimming because of breathing and strength laterality. In this study, the asymmetrical freestyle swimming performance of a male elite level swimmer who breathed every second arm stroke (unilaterally) was investigated. A laser body scan and multi-angle video footage of the athlete were used to generate a swimming biomechanical model. This model was then used in a Smoothed Particle Hydrodynamics (SPH) fluid simulation of swimming through a virtual pool. The results from this study enabled the kinematic asymmetry to be related to the consequential fluid dynamic asymmetry. The intra-cyclic fluctuations in the streamwise forces and speed were also examined. Hand angles of attack were compared along with the lift and drag contributions of the hands to generating the streamwise thrust. From this study, connections between asymmetry and the resultant swimming performance were identified.